2015
DOI: 10.1111/pin.12326
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen and cancers of the colorectum, breast, and lung in postmenopausal women

Abstract: As estrogens play an important role in maintaining physiological function in various organs, the estrogen decrease after menopause is thought to cause various diseases frequently observed in postmenopausal or elderly women. With the aging of society and a decrease in infectious or vascular diseases, neoplasms have now become the most frequent cause of death in Japan. Cancers of the colorectum, breast, and lung have been rapidly increasing both in incidence and death, especially among postmenopausal women. Inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 54 publications
(111 reference statements)
3
15
0
Order By: Relevance
“…It has also been reported that estrogen may have protecting effects against various cancers [9]- [10]. The research revealed that estrogen has improving effects on glioblastoma treatment [11].…”
Section: Discussionmentioning
confidence: 93%
“…It has also been reported that estrogen may have protecting effects against various cancers [9]- [10]. The research revealed that estrogen has improving effects on glioblastoma treatment [11].…”
Section: Discussionmentioning
confidence: 93%
“…The relative dominance of HSD-1 over HSD-2 would accelerate the conversion of E1 into E2, leading to marked condensation of E2 in the frontal tissue (Fig. 1) 12 . Such a high level of estrogens concentrations in the frontal lobe, together with distinct nuclear ER-β1 expression in glias among controls, may add further evidence for the physiologically important role of the estrogen signaling system in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…These observations suggest a protective effect of estrogens against AD; however, in Women’s Health Initiative (WHI) hormone therapy trials, where the effect of external female hormone use was tested against a placebo, the risk of AD was reported to increase in women treated with hormone (estrogen-progesterone combined) replacement therapy, raising controversies in this study area 11 . Generally, in postmenopausal women, where estrogens from the ovary markedly decrease, peripheral estrogen synthesis via estrogen-metabolizing enzymes (EMEs) is important as the source of estrogens 12 . EMEs include aromatase, steroid sulfatase (STS), estrogen sulfotransferase (EST), and some types of 17β-hydroxysteroid dehydrogenase (HSD).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations